VALUATION IRRIGATION OF RICE FARMING AT UPSTREAM AND DOWNSTREAM AREAS IN SPECIAL REGION OF YOGYAKARTA - Habibullah, Triyono1,Aris Slamet Widodo1 (2016)
ABSTRACT This study aims to know Willingness To Pay (WTP) farmers for management and maintenance of irrigation and factors that influence it on rice farming at upstream and downstream areas in Special Region of Yogyakarta. Survey is conducted to 60 respondents, 30 farmers at upstream area and 30 farmers at downstream area. Primary data obtained through questioners and interviews, and then analyzed using multiple linear regression and descriptive analysis. Analysis results show that the WTP average amount of Rp17.500,- at upstream area and Rp11.167 at downstream area. Willingness to pay is influenced significantly by family size, wide land area, irrigation management services, quality of irrigation water and location. There are some farmers in downstream area that will not pay for the irrigation. They opine the water is already in nature as God’s present.